Diffusion-weighted MRI techniques for the evaluation of focal hepatic lesions - Kocakoç, Ercan; Onur, Mehmet Ruhi; Serter, Asli (My University, 2012)
Diffusion-weighted (DW) MRI has been more frequently used in abdominal imaging with the introduction of echo-planar imaging and parallel imaging techniques that reduce the examination time and eliminate time-related artifacts. Detection of focal hepatic lesions can be accomplished by visual assessment of signal changes on DW images. Diffusion characteristics of focal hepatic lesions are represented by quantitative apparent diffusion coefficient values. Utility of DW-MRI as a complementary imaging method in evaluation of focal hepatic lesions depends on comparison between the results of DW-MRI and conventional MRI sequences. Detection and characterization of focal hepatic lesions in DW-MRI will be reliable with the advances in MRI technology that provide high-quality images and avoid artifacts. © 2012 Future Medicine Ltd.
Keywords: abscess; apparent diffusion coefficient; diffusion-weighted MRI; focal nodular hyperplasia; hemangioma; hepatic cyst; hepatic lesion; hepatocellular carcinoma; metastasis